Exploring issues of resilience and technology use for older people - A scoping review protocol (Research, Society and Development, 2022)
The aim of this scoping review is to understand the extent of issues of resilience implied by the interactions of older people with financial, social, and health related technologies. Older people aged 60+, technology use or non-use, and issues of resilience studied over the last four years (2019-2022) demarcate the scope of this review. Key exclusion criteria are older adults living in long-term care facilities, nursing homes, care homes and hospital in-patients. It also excludes studies on the perspectives of older peoples’ clinicians. The review will be carried out according to the Joanna Briggs Institute (JBI) scoping review methodology. The key information sources are SCOPUS, Web of Science, CINAHL, PsychINFO, and MEDLINE databases. The forms of grey literature included are reports from government and non-government organizations, as well as studies from the ProQuest Dissertations & Theses - Global database. The search is limited to studies written in English. For the first step in the search strategy, keywords and index terms will be identified via SCOPUS, Web of Science, and MEDLINE databases. This is followed by a search via the above databases. Third, a search of the reference lists of all included articles will form part of the full-text screening process. Two researchers will independently screen the titles and abstracts of the literature and then read the full text of the included literature, applying the inclusion criteria and searching reference lists. All data will be presented in tables and charts to answer the review question.